1990
DOI: 10.1111/j.1399-3054.1990.tb05675.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene accelerates the breakdown of cytokinins and thereby stimulates rooting in Norway spruce hypocotyl cuttings

Abstract: Cuttings were taken from 4‐week‐old seedlings of Norway spruce (Picea abies L. Karst.) raised at two different irradiation levels. Rooting experiments showed that root formation was increased by the ethylene formed by adding 1‐aminocyclopropane‐1‐carboxylic acid ACC or Ethrel, especially in the slowly rooting cuttings grown under high light (HL). Cobaltousion. an ethylene synthesis inhibitor, delayed rooting, especially in the easily rooted cuttings grown under low light (LL). Compounds isolated from the cutti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 22 publications
0
24
0
2
Order By: Relevance
“…For instance, ethylene inhibited adventitious root formation in pea (Pisum sativum) cuttings (Nordström and Eliasson, 1984) and Prunus avium explants (Biondi et al, 1990), whereas it stimulated root initiation in cuttings of Picea abies (Bollmark and Eliasson, 1990). Also, experimental conditions seem to matter, as contrasting results were found in various studies on mung bean (Vigna radiata -e.g., Robbins et al, 1983 vs. Geneve andHeuser, 1983).…”
Section: Involvement Of Ethylenementioning
confidence: 56%
“…For instance, ethylene inhibited adventitious root formation in pea (Pisum sativum) cuttings (Nordström and Eliasson, 1984) and Prunus avium explants (Biondi et al, 1990), whereas it stimulated root initiation in cuttings of Picea abies (Bollmark and Eliasson, 1990). Also, experimental conditions seem to matter, as contrasting results were found in various studies on mung bean (Vigna radiata -e.g., Robbins et al, 1983 vs. Geneve andHeuser, 1983).…”
Section: Involvement Of Ethylenementioning
confidence: 56%
“…These promoting effects of auxin and ethylene are commonly found with respect to adventitious root formation in soft-and hard-wooded cuttings (e.g. Gurumurti, Gupta and Kumar, 1985;Robbins et al, 1985;Bollmark and Eliasson, 1990;Nordstrom and Eliasson, 1991;Selby, Kennedy and Harvey, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…and Douglas fir. On the other hand, Bollmark and Eliasson (1990) concluded that the enhanced rooting of Norway spruce (P. abies) hypocotyl cuttings, promoted by the treatment with ACC or Ethrel, was attributed to the ethylene-mediated acceleration of the breakdown of cytokinins.…”
Section: Ethylenementioning
confidence: 99%